2014
DOI: 10.1016/j.ejop.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between protozoan and metazoan communities and operation and performance parameters in a textile sewage activated sludge system

Abstract: The present study aims at investigating the possibility of assessing performance and depuration conditions of an activated sludge wastewater treatment plant through an exploration of the microfauna. The plant, receiving textile industrial (70%) and domestic (30%) sewage, consists of a two-step biological depurating plant, with activated sludge followed by a percolating system. A total of 35 samples were analyzed during five months, and 30 taxa of protozoa and small metazoa were found. Epistylis rotans, Vortice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…With a relatively short retention time of biomass in the bioreactor (WTP1 and WTP2) and too short aeration (WTP2), the SBI was systematically reduced to the lowest class of sludge quality. The mentioned correlation has been noted, among others, by dos Santos et al, [37] while conducting research on textile wastewater treatment (70% industrial sewage and 30% domestic sewage). He demonstrated that the temporal variability of the sludge biotic index was well correlated not only with sludge concentration and dissolved oxygen concentration, but also with the inflow of total suspended solids.…”
Section: Discussionmentioning
confidence: 92%
“…With a relatively short retention time of biomass in the bioreactor (WTP1 and WTP2) and too short aeration (WTP2), the SBI was systematically reduced to the lowest class of sludge quality. The mentioned correlation has been noted, among others, by dos Santos et al, [37] while conducting research on textile wastewater treatment (70% industrial sewage and 30% domestic sewage). He demonstrated that the temporal variability of the sludge biotic index was well correlated not only with sludge concentration and dissolved oxygen concentration, but also with the inflow of total suspended solids.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have demonstrated the correlation of the performance parameters of activated sludge wastewater treatment plants through the exploration of microfauna (specific microbial taxa) (FRYER;GRAY, 2012;SANTOS et al, 2014;CASTILLO;MEDINA;CONTRERAS, 2016;CYDZIK-KWIATKOWSKA;ZIELIŃSKA, 2016;AMARAL et al, 2018). As activated sludge microbial communities vary widely based on plant operating technology, influent characteristics, and treatment plant capacity (AMARAL et al, 2018;BEGMATOV et al, 2022), research on the identification of microbial species in activated sludge systems, especially in agricultural industrial sewage stations, is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Protozoa, fungi and metazoans are part of the large microbial eukaryotic community playing a significant role in wastewater treatment systems. They contribute to improve physicochemical and microbiological effluent quality parameter by enhancing the sludge production and sedimentation [108,197,198]; removing contaminants [199,200], and significantly contributing to the pathogenic microorganisms removal [201,202]. The evolutionary eukaryotic classification is continuously growing [134,136,203], helping to identify more extensive groups of organisms that are either present but not easy to perceive under (optical, fluorescent or scanning electron) microscopy [204,205] or that they were morphologically classified into inaccurate taxonomic groups [206,207].…”
Section: Introductionmentioning
confidence: 99%